Expectations of Exchange Rates and Differential Inflation Rates: Further Evidence on Purchasing Power Parity in Efficient Markets - Huang, Roger D. (Journal of Finance, 1987)
The paper tests the null hypothesis of ex ante purchasing power parity. The empirical evidence obtained is inconsistent with the null for major industrialized countries over the current floating exchange rate regime. Expected nominal exchange rate changes appear to deviate systematically from expected inflation rate differentials over the same holding period even though real exchange rate changes appear to be serially uncorrelated. This supports the presence of time-varying risk premia in foreign exchange markets and real determinants of exchange rate movements as suggested by equilibrium theories of international asset markets.